COVID-19 concerns, influenza vaccination history and pregnant women’s COVID-19 vaccine acceptance: a systematic review - Chiquita Febby Pragitara; Naomi Rahmasena; Ayuning Tetirah Ramadhani; Sarah Fauzia; Reyna Erfadila; Dadang Mutha Wali Faraj; Diah Caesaria Garindra Rahmadhanti; Samsriyaningsih Handayani (Intelektual Pustaka Media Utama, 2022)
Pregnant women have a higher risk of serious illness during the coronavirus disease 2019 (COVID-19) pandemic. This raises concerns about COVID-19 infection in pregnant women. Other than COVID-19, pregnant women are also a high-risk group for influenza infection. Influenza vaccination is used to prevent coinfection with COVID-19. Thus, this study examined the acceptance of the COVID-19 vaccine in pregnant women based on factors of worry about COVID-19 infection and a history of influenza vaccination. This study was a systematic review that assessed cross-sectional articles of the year 2020-2021 from the Pubmed, Science Direct, and Medrxiv databases with narrative analysis. There were three articles that met the criteria. The three articles showed significant relationships between concerns of being infected with COVID-19 and receiving COVID-19 vaccine acceptance in pregnant women, while a significant relationships between a history of influenza vaccination and accepting COVID-19 vaccination in pregnant women were only found in two articles. Compared to the history of influenza vaccination, the concerns of being infected with COVID-19 in pregnant women were significantly more related to accepting COVID-19 vaccination, so it can be the focus of intervention to increase the acceptance of COVID-19 vaccination in pregnant women.